Analysis of Anxiety Levels in End-Stage Kidney Disease Pa-tients Under Dialysis Therapy - Adi, Ginanjar Sasmito; Hamid, M. Ali (Universitas Muhammadiyah Jember, 2024)
End-stage renal disease has a profound impact on both the physiological and psychological aspects of patients. The consequences of end-stage renal disease extend to anxiety, influenced by the symptoms encountered and the side effects resulting from hemodialysis therapy, which, in turn, affects life expectancy and adherence to disease management. This study aims to investigate anxiety levels in individuals with chronic kidney disease undergoing dialysis. This descriptive analytic study involved a total of 45 respondents undergoing hemodialysis therapy at Jember Klinik Hospital. The instruments utilized included an observational form and the Hamilton Anxiety Rating Scale. The findings revealed varying levels of anxiety, with severe anxiety at 33.3%, moderate anxiety at 31.1%, mild anxiety at 22.2%, and no anxiety at 13.3%. In the anxiety variable, among the 14 observation items on the HARS instrument, the most pronounced disturbances were observed in tension, depression, cardiovascular symptoms, and respiratory symptoms. Anxiety remains a prevalent psychological symptom among many end-stage renal patients. Strategies should be implemented to mitigate anxiety in patients, thereby improving their quality of life and reducing mortality